The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ijms18040807
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Accelerates Cell Proliferation and Increases the Secretion and mRNA Expression of Osteopontin in Human Pancreatic Duct Epithelial Cells

Abstract: Background: The incidence of pancreatic cancer is increasing year-by-year in Japan. Among the diseases that complicate pancreatic cancer, diabetes is the most common. Recently, it has become evident that patients suffering from diabetes and obesity show increased expression of osteopontin (OPN). The purpose of this study was to investigate the effect of high glucose and high insulin culture conditions on a human pancreatic duct epithelial cell line (HPDE-6), focusing particularly on OPN expression. Methods: HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…There is a 1.5- to 2.0-fold increase in the risk of developing pancreatic cancer in type 2 diabetes mellitus patients [146,147]. The hyperglycemia, which is caused by insulin resistance and inability to suppress inappropriate hepatic glucose release, has been shown to enhance proliferation [148,149], promotes epithelial–mesenchymal transition and cancer stem cells’ properties [150], and metastatic potential in pancreatic cancer [151,152]. Recently, it has been reported that high glucose concentrations in the cell culture medium induce the KRAS G12D mutation in vitro.…”
Section: Pancreatic Cancer and Diabetesmentioning
confidence: 99%
“…There is a 1.5- to 2.0-fold increase in the risk of developing pancreatic cancer in type 2 diabetes mellitus patients [146,147]. The hyperglycemia, which is caused by insulin resistance and inability to suppress inappropriate hepatic glucose release, has been shown to enhance proliferation [148,149], promotes epithelial–mesenchymal transition and cancer stem cells’ properties [150], and metastatic potential in pancreatic cancer [151,152]. Recently, it has been reported that high glucose concentrations in the cell culture medium induce the KRAS G12D mutation in vitro.…”
Section: Pancreatic Cancer and Diabetesmentioning
confidence: 99%
“…A meta-analysis has shown that an elevated serum OPN level might be used as a promising diagnostic tool for early identification of PC [ 123 ]. In addition, a recent study has reported that high glucose levels accelerated cell proliferation and increased the secretion of OPN in human pancreatic duct epithelial cells [ 124 ]. However, another study has reported that the presence of OPN in PC might have a protective effect independent of tumor stage [ 125 ], and a recent study has concluded that the relationship between OPN and PC remained unclear [ 126 ].…”
Section: The Association Of Opn With Apoptosis In Inflammatory Gi mentioning
confidence: 99%
“…In addition to its catabolic role, glucose is used for the synthesis of nucleotides through the pentose phosphate pathway, which is essential to produce ribose for DNA synthesis during cell division. Proliferating cells, such as cancer cells, prefer glucose as fuel to support their rapid proliferation ( Han et al, 2011 ; Jones and Schulze, 2012 ; Ito et al, 2017 ; Luo et al, 2018 ; Zhou et al, 2018 ). For these reasons, it is believed that the media of various cultured cells require high concentrations of glucose to improve cell proliferation.…”
Section: Introductionmentioning
confidence: 99%